Profil dermatomikosis superfisial pada pekerja pabrik tahu di Desa Mabar, Kecamatan Medan Deli - Jamaliyah dr; Meidina K. Wardani; Irma D Roesyanto (Fakultas Kedokteran USU, 2013)
Introduction : Superficial dermatomycosis is a fungal infection of the skin, nails and hair, caused by dermatophytes and non-dermatophytes. Factors that predisposing, one of which is exposed to water due to work. Tofu industry knows as a small industry engaged in the informal sector. In the industry, at this stage of the manufacturing process,the factory workers are often exposed to water of doing his work.To know the superficial dermatomycosis profil of tofu industries workers in Mabar Village Medan Deli.Methods : This study is adescriptivesurvey study with cross-sectional design. The study population is all of the employees in nine factories in Mabar Village Medan Deli.Result : Among 72 participants, 18 suffered from superficial dermatomycosis, the proportion was 25%. We obtained 11 workers suffered from cutaneousintertriginous candidiasis, 5workers suffered from tineapedis and 2 workers suffered from tinea pedis and onychomycosis. We obtained Candida sp, Aspergillusfumigatus and M. gypseumas causative agents.Conclusion : In this study, the proportion of superficial dermatomycosis was 25%,the most common superficial dermatomycosis(61.11%) was cutaneous intertriginous candidiasis and Candida spas causative agents.Keywords : superficial dermatomycosis;tofu industries workers